The role of the multidisciplinary team in managing a challenging brittle bone disease with 18 fractures in the modern era: a case report and literature review - Ramu, Sivalakshmi; Das, Anamika; Zangmo, Rinchen (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Osteogenesis imperfecta (OI) is a rare autosomal dominant disorder due to collagen type I biosynthesis defects. It aggressively affects maternal and fetal outcomes in pregnancy. In this case report, we will be discussing the course of pregnancy in an OI patient who has already had 18 fractures since childhood and the challenges faced during the course. A 29-year-old primigravida who was diagnosed with OI since childhood had approximately 18 fractures up to the age of 29. She was under regular antenatal follow-up in our clinic. She was diagnosed with late-onset stage 1 fetal growth restriction at 36 weeks. She was planned for an elective caesarian under a multidisciplinary team at 37 weeks given her short stature, contracted pelvis, and stage 1 fetal growth restriction. She had an uneventful delivery course without any intraoperative and postoperative complications. There was no stress fracture post-delivery, and the newborn developed normally during a 1-year follow-up period. This case highlights the management of OI in pregnancy who had a history of multiple fractures and also emphasizes the need for a tertiary care center in the management of these high-risk patients. A close follow-up of these patients with prenatal genetic testing, regular ultrasound monitoring, and a multi-disciplinary team will aid in an early diagnosis of all the potential underlying complications, thereby leading to favorable maternal and fetal outcomes. A literature review on this topic is also presented.